Regioselective acylation of resveratrol catalyzed by lipase under microwave - Zhi Wang (Green Chemistry Letters and Reviews, 2018)
The enzymatic regioselective acylation of resveratrol was achieved in organic solvents catalyzed by the lipase from Candida sp. 99–125 (CSL) under microwave irradiation. Influences of various reaction conditions have been studied. After selecting the optimum conditions [MTBE (20 ml, aw = 0.38), resveratrol (0.1 mmol), vinyl acetate (1.0 mmol) and CSL (100.0 mg) under microwave irradiation (35°C, 400 W)], CSL exhibited a satisfied enzyme activity (281 ± 11 μmol/g/h) and yield of 75% for 4′-O-acetyl- resveratrol could be obtained in about 4 h when performing the reaction on a 25-fold-larger scale. Schematic illustration of the enzymatic regioselective acylation of resveratrol catalyzed by the lipase from Candida sp. 99–125 (CSL) under microwave irradiation.